Do development projects crowd out private-sector activities? A survival analysis of contract farming participation in northern Ghana - Lambrecht, Isabel B.; Ragasa, Catherine (International Food Policy Research Institute, 2016)
Contract farming (CF) is attractive as a possible private-sector-led strategy for improving smallholder farmers’ welfare. Yet many CF schemes suffer from high turnover of participating farmers and struggle to survive. So far, the dynamics of CF participation have remained largely unexplored. We employ duration analysis to examine factors affecting entry into and exit from different maize CF schemes in northern Ghana, focusing specifically on the impact of development projects on CF entry and exit. We find that agricultural development projects reduce the likelihood of scheme entry and increase the likelihood of exit. Our findings confirm concerns that, if interventions are not planned in accordance with relevant private-sector actors, private-sector initiatives can be hindered by competing development projects.